2019
DOI: 10.14710/jitaa.44.2.155-166
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to combat the deleterious impacts of heat stress through feed restrictions and dietary supplementation (vitamins, minerals) in broilers

Abstract: The objective of the current study was to evaluate the impacts of feed restriction (FR) for 3 hours and/or dietary supplementation with vitamins and minerals on growth, mortality rate, some carcass traits, and serum biochemistry indices of broiler chicks under heat stress in the open housing system. A total of 240 one-week old broilers were weighed and randomly assigned into 4 equal experimental treatments. Treatment 1 (T1) was fed ad libitum on basal diets, T2 birds were fed on basal diets with FR, T3 birds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In this practice, feed intake is reduced by withdrawing feed for a certain period (generally 8 a.m. to 5 p.m.) to reduce the metabolic rate of birds. Feed restriction is found to reduce rectal temperature, minimize mortality [ 37 , 38 ] and decrease abdominal fat [ 39 ] in heat-stressed broilers. Uzum et al [ 38 ] found that restricting the availability of feed to 8 h a day during the hot periods in broilers improved feed efficiency and shortened tonic immobility; a measure to determine fearfulness in which birds are placed on its back for observing righting reflex.…”
Section: Potential Strategies To Mitigate Heat Stress In Poultrymentioning
confidence: 99%
“…In this practice, feed intake is reduced by withdrawing feed for a certain period (generally 8 a.m. to 5 p.m.) to reduce the metabolic rate of birds. Feed restriction is found to reduce rectal temperature, minimize mortality [ 37 , 38 ] and decrease abdominal fat [ 39 ] in heat-stressed broilers. Uzum et al [ 38 ] found that restricting the availability of feed to 8 h a day during the hot periods in broilers improved feed efficiency and shortened tonic immobility; a measure to determine fearfulness in which birds are placed on its back for observing righting reflex.…”
Section: Potential Strategies To Mitigate Heat Stress In Poultrymentioning
confidence: 99%
“…Food digestion and the metabolic heat generated add significantly to the heat load of rapidly growing meat birds. Withdrawing feed (FW) during the hottest period of the day reduces metabolic rate, decreasing heat production, body temperature, mortality and abdominal fat in hightemperature challenged broiler chickens (Francis et al 1991;Abhu-Dieyeh 2006;Mohamed et al 2019). Removal of feed for a period of hours before or during a high-temperature challenge can improve performance of broiler chickens (Francis et al 1991;Ait-Boulahsen et al 1993;Hiramoto et al 1995;Mohamed et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Withdrawing feed (FW) during the hottest period of the day reduces metabolic rate, decreasing heat production, body temperature, mortality and abdominal fat in hightemperature challenged broiler chickens (Francis et al 1991;Abhu-Dieyeh 2006;Mohamed et al 2019). Removal of feed for a period of hours before or during a high-temperature challenge can improve performance of broiler chickens (Francis et al 1991;Ait-Boulahsen et al 1993;Hiramoto et al 1995;Mohamed et al 2019). Other studies have reported poorer performance using this strategy (Lozano et al 2006;Abhu-Dieyeh 2006;Uzum and Toplu 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the broiler production performance was affected negatively (Wasti et al, 2020). Furthermore, heat-stressed broilers have shown an increase in abdominal fat and a loss in carcass protein due to heat stress (Mohamed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%